Additional file 10 of Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark (13318734) (2025)
Additional file 10. Table S7—Distribution of multigenic family members responding to VHSV across L1, L2 and L3 lists.